SEC31A mutation affects ER homeostasis, causing a neurological syndrome. Issue 3 (21st November 2018) - Halperin, Daniel; Kadir, Rotem; Perez, Yonatan; Drabkin, Max; Yogev, Yuval; Wormser, Ohad; Berman, Erez M; Eremenko, Ekaterina; Rotblat, Barak; Shorer, Zamir; Gradstein, Libe; Shelef, Ilan; et al.
Abstract : Background: Consanguineous kindred presented with an autosomal recessive syndrome of intrauterine growth retardation, marked developmental delay, spastic quadriplegia with profound contractures, pseudobulbar palsy with recurrent aspirations, epilepsy, dysmorphism, neurosensory deafness and optic nerve atrophy with no eye fixation. Affected individuals died by the age of 4. Brain MRI demonstrated microcephaly, semilobar holoprosencephaly and agenesis of corpus callosum. We aimed at elucidating the molecular basis of this disease. Methods: Genome-wide linkage analysis combined with whole exome sequencing were performed to identify disease-causing variants. Functional consequences were investigated in fruit flies null mutant for the Drosophila SEC31A orthologue. SEC31A knockout SH-SY5Y and HEK293T cell-lines were generated using CRISPR/Cas9 and studied through qRT-PCR, immunoblotting and viability assays. Results: Through genetic studies, we identified a disease-associated homozygous nonsense mutation in SEC31A . We demonstrate that SEC31A is ubiquitously expressed, and that the mutation triggers nonsense-mediated decay of its transcript, comprising a practical null mutation. Similar to the human disease phenotype, knockdown SEC31A flies had defective brains and early lethality. Moreover, in line with SEC31A encoding one of the two coating layers comprising the Coat protein complex II (COP-II) complex, trafficking newly synthesised proteins from the endoplasmic reticulum (ER) to the Golgi, CRISPR/Cas9-mediated SEC31A null mutant cells demonstrated reduced viability through upregulation of ER-stress pathways. Conclusion: We demonstrate through human and Drosophila genetic and in vitro molecular studies, that a severe neurological syndrome is caused by a null mutation in SEC31A, reducing cell viability through enhanced ER-stress response, in line with SEC31A's role in the COP-II complex.